SOME NOTES ABOUT THE CONSTRUCTION OF A MECHANISTIC LANDSCAPE OF NATURE (Revista Brasileira de Ensino de Ciências e Matemática, 2025)
This article analyzes the process of constitution of the mechanistic landscape of nature through the development of formal methods linked to experimental practice with a view to describing phenomena, combined with philosophical speculations. With the development of the metalanguage of science, mathematical formulations gradually began to be used to describe phenomena in the physical world, based on the observation of regularities in nature. The mechanistic landscape of nature that was being formed underwent transformations resulting from experimental observations, studies on languages, cultural studies and work in neurosciences about human behavior and the influence of the environment. The sources consulted were scientific articles and books written by scientists from the modern period onwards.